Preparation and characterization of PVDF/CaCO3 composites - Campos, Joao Sinezio de C.; Ribeiro, Alexandre A.; Cardoso, Celso Xavier (Elsevier B.V., 2007)
The contribution of new materials, involving composites and blends, has been reaching the most varied fields of science, as much of the scientific as technological point of view. This is due to the man's needs in applications, especially in medicine areas. Thus, this work shows the preparation and characterization of poly(vinylidene fluoride) (PVDF) and calcium carbonate (CaCO3) Composite films in order to analyse the incorporation of CaCO3 in PVDF for future application in bony restoration and bony filling. The films were prepared by casting method, where the PVDF pellet shape was dissolved in dimethylacetamide (DMA) and in a separate container CaCO3/DMA emulsion was also made. Soon afterwards they were mixed in several proportions 100/00, 95/05, 85/15, 70/30 in weight and left to dry in greenhouse. Homogeneous and flexible films were obtained and structurally characterized by attenuated total reflection infrared spectroscopy (FT-IR/ATR), thermal analyses (DSC, TGA), X-ray diffractometry, optical and scanning electron microscopies. The results showed that the material was a composite with good thermal stability until around 400 degrees C, the crystallinity of PVDF was non-polar alpha-phase and the obtained films were porous, being these filled with CaCO3. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: poly(vinylidene fluoride); polymer composites; biopolymers; biomaterials; calcium carbonate